2010
DOI: 10.1111/j.1529-8817.2010.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYCOBILIN CONTENT OF THE CONCHOCELIS PHASE OF ALASKAN PORPHYRA (BANGIALES, RHODOPHYTA) SPECIES: RESPONSES TO ENVIRONMENTAL VARIABLES1

Abstract: Variations of pigment content in the microscopic conchocelis stage of four Alaskan Porphyra species were investigated in response to environmental variables. Conchocelis filaments were cultured under varying conditions of irradiance and nutrient concentrations for up to 60 d at 11°C and 30 psu salinity. Results indicate that conchocelis filaments contain relatively high concentrations of phycobilins under optimal culture conditions. Phycobilin pigment production was significantly affected by irradiance, nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…In contrast, under experimental conditions, Noisette et al (2013) found that the chlorophyll a concentration of the temperate rhodolith algae Lithothamnion corallioides was unaffected by temperature, while carotenoid concentration decreased with temperature. The interaction of environmental variables such as irradiance, nutrients (Lin and Stekoll, 2011), and temperature (Kim et al, 2007), has an effect on pigment production. However, previous studies have found that the biochemical response to these variables is highly species specific (see Kim et al, 2007;Lin and Stekoll, 2011;Stengel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, under experimental conditions, Noisette et al (2013) found that the chlorophyll a concentration of the temperate rhodolith algae Lithothamnion corallioides was unaffected by temperature, while carotenoid concentration decreased with temperature. The interaction of environmental variables such as irradiance, nutrients (Lin and Stekoll, 2011), and temperature (Kim et al, 2007), has an effect on pigment production. However, previous studies have found that the biochemical response to these variables is highly species specific (see Kim et al, 2007;Lin and Stekoll, 2011;Stengel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of environmental variables such as irradiance, nutrients (Lin and Stekoll, 2011), and temperature (Kim et al, 2007), has an effect on pigment production. However, previous studies have found that the biochemical response to these variables is highly species specific (see Kim et al, 2007;Lin and Stekoll, 2011;Stengel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They probably promote cell enlargement, cell division or have some other cellular and molecular effects. IAA at 0.4 ppm, and kinetin at 0.8 ppm promoted the growth of Porphyra conchocelis stage (Lin and Stekoll 2007).…”
Section: Chemicals Stimulatory To Spore Germinationmentioning
confidence: 99%
“…These studies were carried out primarily on material from Sunshine Cove, hence the decision to select a specimen from that location rather than the Aleutian Islands as the type of the species. called this species Unknown #2, and Lin and Stekoll (2011), Porphyra sp.…”
Section: Discussionmentioning
confidence: 99%